Pharmacokinetic Assessment of a Fast-release Orodispersible Tramadol Tablet Compared to a Conventional Tramadol Capsule - Tagarro, Ignacio; Vauzelle-Kervroedan, Francoise; Díez, Mary Carmen (Arzneimittelforschung, 2004)
The purpose of this clinical trial was to compare the pharmacokinetics of a recently developed fast-release orodispersible tramadol tablet (CAS 27203-92-5, Zamadol® Melt) to that of a conventional tramadol capsule. This new formulation, once placed into the mouth, disintegrates rapidly in contact with the saliva. Therefore, when the saliva is swallowed, the drug reaches the gastrointestinal tract.In an open, randomised, two-period, crossover study performed in 20 healthy volunteers, the orodispersible tramadol tablet and a conventional tramadol capsule were administered. Even although the galenics of both products are far different, statistical analysis of pharmacokinetic parameters allows concluding bio-equivalence, not only for the parent molecule (tramadol), but also for its active metabolite O-desmethyl tramadol.This orally dispersible formulation, being bioequivalent to the standard capsules so far used, has the practical advantage that it can be taken without liquids. This facilitates an early treatment of emergent pain, irrespective of the place or situation where it may arise.
Keywords: CAS 27203-92-5; Tramadol, orodispersible, pharmacokinetics; Zamadol® Melt, bioavailability, bioequivalence, drug delivery